Characterization of Epicoccum isolates obtained from Argentinean sorghum grain samples - Hipperdinger, Marcela Liliana (2024)
Sorghum has numerous agronomic advantages, a great economic importance in food production and various industrial applications. Itsconsumption has increased in the last ten years and probably its importance may even increase in the future, considering its relationship withglobal warming since this plant is less demanding with water. However, its productivity is affected by various fungal diseases with the productionof mycotoxins that cause great economic losses. Alternaria, Epicoccum and Pyricularia genera are the main fungal contaminants in sorghumgrains, and recognized producers of tenuazonic acid, a mycotoxin previously found in assayed sorghum samples in the Mycology andMycotoxicology laboratory belonging to the Center for Research and Development in Industrial Fermentations. Fungal isolates obtained fromthese sorghum grains from the National Institute of Agricultural Technology (INTA, Manfredi, Córdoba, Argentina) were characterized using apolyphasic approach based on morphological and genetic characteristics and in the ability to produce mycotoxins. Morphological analysissuggested the identity of Epicoccum sorghinum, which was later confirmed by molecular analysis. The ability of these isolates to producetenuazonic acid was evaluated and it was determined that 65% of the studied isolates produced tenuazonic acid at variable levels. This is the firststudy that provides a molecular approach to E. sorghinum isolates in Argentina and clearly confirms the wide genetic and phenotypic variabilitypreviously reported for this species in other countries. The presence of these tenuazonic acid-producing isolates in sorghum grains represent aneconomic and health problem for Argentina that it is considered one of the main exporters worldwide.